Barriers and enablers of integrated care in the UK: a rapid evidence review of review articles and grey literature 2018–2022 - Thomson, Linda J. M.; Chatterjee, Helen J. (Frontiers in Public Health, 2024)
Integrated care refers to person-centered and coordinated, health and social care and community services. Integrated care systems are partnerships of organizations that deliver health and care services which were placed on a statutory footing in England, April 2022. Due to the need for fast, accessible, and relevant evidence, a rapid review was conducted according to World Health Organization methods to determine barriers and enablers of integrated care across UK nations, 2018-2022. Nine databases were searched for review articles reporting evaluation of integrated care interventions, quality checked with CASP. OpenGrey and hand searches were used to identify grey literature, quality checked with AACODS. Thirty-four reviews and 21 grey literature reports fitted inclusion criteria of adult physical/mental health outcomes/multiple morbidities. Thematic analysis revealed six themes (collaborative approach; costs; evidence and evaluation; integration of care; professional roles; service user factors) with 20 subthemes including key barriers of cost effectiveness; effectiveness of integrated care; evaluation methods; focus of evidence; future research; and impact of integration; and key enablers of accessing care; collaboration and partnership; concept of integration; co-production and coordination; inter-professional relationships; and person-centered ethos. Findings indicated paucity of robust research to evaluate interventions and lack of standardized methodology to assess cost effectiveness, although growing interest in coproduction engendered information sharing and reduced duplication, and inter-professional collaborations bridged task-related gaps and overlaps. The importance of identifying elements of integrated care associated with successful outcomes and determining sustainability of interventions meeting joined-up care and preventive population health objectives was highlighted.